DESIGN OF PRESSURE MEASUREMENT IN THE EXERCISE SMART MINE USING A PRESSURE SENSOR - Endin Tri Hartanto; Edy Widodo; Ayip Rivai Prabowo; Sulaiman Sulaiman (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2020)
The Sea Mines are explosive devices placed in the waters to destroy ships or submarines. The sea mines were placed in the water depths and waited until it was triggered to be blown up by an approaching enemy vessel. The waves in the leave can be measured using the air pressure sensor placed below the water surface, the change in the sensor up and down will result in changes in air pressure. Changes in the resulting pressure of the vessel will result in water waves, resulting from changes in the water wave height will result in a change in water pressure gauge sensors in the air. The MPX5700 air pressure Sensor, as a source of pressure measurement with analog voltage output is comparable to the large value of air pressure. Design the air pressure measuring instrument system using the Arduino microcontroller as the unit of the voltage conversion process to the pressure variable in the KPA. On testing authors use applications that are created using Visual Studio 2012 to plotting the pressure graphs and large voltage output sensors. Results obtained using the MPX5700 sensor with an analog output can result in a linear pressure output with a large voltage output, from the test result obtained the conversion value 0.2 V as the value of 0 Kpa and the value of 4.7 V asthe maximum value pressure measurement of 700 Kpa. Keywords: mines, MPX5700, Arduino microcontrollers